PERANCANGAN MODEL EKONOMI KREATIF 5.0 BERBASIS DIGITAL SOCIAL INNOVATION - Bagas Brian Pratama; Dian Wijayanti (Jurnal Fokus Manajemen Bisnis, 2023)
Shifts in social, community, economic and cultural life continue to occur following the development of the digital world. This study aims to design a model for the development of the creative economy in the era of society 5.0 in Indonesia. The research method uses literature study with four main stages, namely library data search, information identification, comparative analysis, and in-depth analysis and conclusion analysis. The design of the model uses the Digital Social Innovation (DSI) framework approach which emphasizes the combination of three forming elements, namely digitalization, innovation, and social. The results of this study provide an overview of the creative economy development model as the main actor that can solve social problems in society through the use of technology. In the era of society 5.0, creative economy actors must have the sensitivity to feel, identify, and map social problems so that they are able to generate ideas, strategies, and innovate appropriate solutions supported by the use of digital technology.